Pandangan Dunia Pengarang Dalam Novel Max Havelaar Karya Multatuli Dan Relevansinya Sebagai Bahan Pembelajaran Sastra Di SMA/ SMK - I Gusti Ayu Intan Maha Utami Dewi; I Made Sujaya; I Kadek Adhi Dwipayana (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study uses the novel Max Havelaar by Multatuli. The problems discussed in this study are, (1) The structure of Multatuli's Max Havelaar novel? (2) The author's world view in the novel Max Havelaar by Multatuli? (3) The relevance of Multatuli's novel Max Havelaar as literature learning material in SMA/SMK?. The aims of this study were (1) to find out the structure of Multatuli's Max Havelaar novel, (2) to find out the world views in Multatuli's Max Havelaar novel, (3) to find the relevance of Multatuli's Max Havelaar novel as material for learning literature in class XII in senior high school. /SMK. The data analysis technique used is the dialectical method. The results of this research analysis can be interpreted in three ways, namely first, the structure in this study is thematic in nature, which means determining the relationship between characters. Second, the researcher finds that Max Havelaar's novel expresses a worldview in the form of Multatuli's ideas and aspirations regarding the phenomenon of colonialism practices towards indigenous peoples. Third, Multatuli's novel Max Havelaar can be made as literature learning material, especially at the high school/vocational school level. This can be measured through three aspects consisting of the language aspect, the latest psychological aspect in the novel, and the historical background aspect. Therefore, the teacher suggests using this novel as material for learning literature for class XII at SMA/SMK